Developing DIGCONAR (Digital Comic Narrative) As An Alternative Media for Teaching Writing Narrative Text in Pandemic Covid - 19 Period - Eka Wulandari; Sri Utami Dewi (STKIP PGRI Trenggalek, 2021)
This research was to develop DIGCONAR learning media. R&D was the design of this research, which aims to develop educational products. In this research, there are five steps, namely need analysis, studying recent theories of education product development, developing the educational product, validating educational product, and field-testing educational product. In addition, a quasi-experimental design was used in this research to obtain data. The sample used was students X grade of SMA Negeri 2 Trenggalek 2020/2021 academic year, 36 students of MIPA 2 and X MIPA 3. The instruments that use in this research are questionnaire, interview, pre-test and post-test. To obtain the data, researchers used instruments in the form of questionnaires, interviews, pre-test and post-test. Data processing is carried out qualitative and quantitative way. The result of need analysis score was 4112. Then, the result of field-testing was 3341 it shows that students strongly agree with the product of DIGCONAR. The result of t-test; the sig.(2-tailed) showed 0.000 < 0.05 in post-test result, so it can be conclude that Ho is rejected meanwhile Ha is accepted. From description above, it means that DIGCONAR was an effective learning media for teaching writing narrative text in pandemic Covid-19 period